Therapeutic potential of popular fermented dairy products and its benefits on human health - Saleem, Gul Naz; Gu, Ruixia; Qu, Hengxian; Bahar Khaskheli, Gul; Rashid Rajput, Imran; Qasim, Muhammad; Chen, Xia (Frontiers in Nutrition, 2024)
In the current arena of time, the transformation of society has improved the standard of living in terms of lifestyle and their nutritional demands and requirements. The microorganisms under controlled conditions and the enzymatic transformation of dietary components are the processes that resulted in fermented foods and beverages. Fermented dairy products with high nutritional value are "the pearls of the dairy industry". During fermentation, fermented dairy products produce bioactive compounds and metabolites derived from bacteria. Research indicates the beneficial effects of probiotics found in dairy products on human health is making lightning-fast headway these days. The utilization of lactic acid bacteria as probiotics for the prevention or treatment of disease has been a driving force behind the discovery of novel potential probiotics found in naturally fermented milk. Probiotics such as lactic acid bacteria and bifidobacteria found in fermented dairy products have a variety of health benefits, including innate immune enhancement, diarrhea treatment, inflammatory bowel disease, diabetes, Tuberculosis, and obesity, relieving irritable bowel disease symptoms, preventing cancer, improving lactose tolerance, lowering cholesterol, enhancing antioxidant activity, and antimicrobial activity against pathogens. This review aims to evaluate the therapeutic efficacy and nutritional and microbiological properties of popular fermented dairy products and their health benefits.